Implementasi Sistem Pemesanan Berbasis Digital pada Sebuah Bengkel - Imansyah, Mohamad Fikri (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
HKU Surabaya Performance Workshop, a micro, small, and medium enterprise (MSME) operating in motorcycle maintenance and repair services in the Tropodo area, faces challenges in expanding its market reach and improving operational efficiency. Analysis indicates that the current business model relies heavily on walk-in customers, thereby limiting growth opportunities. Based on observations and interviews with the business owner, this article proposes a business model transformation by introducing a mobile motorcycle service supported by a digital ordering system via WhatsApp. Additionally, a Standard Operating Procedure (SOP) has been developed to ensure consistent and high-quality service delivery. This strategy is expected to address existing constraints, broaden customer outreach, and enhance competitiveness in an increasingly digital market. The adoption of a flexible, technology-driven business model is projected to be a strategic step toward achieving long-term growth for MSMEs in the automotive sector.